1995
DOI: 10.1038/bjc.1995.9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced topoisomerase II activity in multidrug-resistant human non-small cell lung cancer cell lines

Abstract: Brsh J_suI d Caner (1.95) 71, [40][41][42][43][44][45][46][47] 00io © 1995 ocdktn Press Al rnghts rserved 0007-0920/95 $9.00 Reduced topoisomerase II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…15) In contrast, decreased levels of Topo IIα gene expression are associated with resistance to Topo II inhibitors in lung cancer cell lines. [8][9][10] These results suggest that Topo IIα gene expression plays an important role in the action of Topo II inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) In contrast, decreased levels of Topo IIα gene expression are associated with resistance to Topo II inhibitors in lung cancer cell lines. [8][9][10] These results suggest that Topo IIα gene expression plays an important role in the action of Topo II inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that decreased levels of Topo II gene expression are associated with resistance to Topo II inhibitors in some cancer cell lines. [8][9][10][11][12] Topo II inhibitors, such as etoposide, are widely used in lung cancer chemotherapy, but small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) show different sensitivity to them. 13,14) Previously we have demonstrated that sensitivity to etoposide, etoposide uptake, and the activity and content of Topo II are higher in SCLC cell lines than in NSCLC cell lines.…”
mentioning
confidence: 99%
“…In the case of doxorubicin selection, the supplementary resistance mechanism probably consists of alterations in topo Ila. Most of the MDR variants selected for doxorubicin resistance contained decreased topo Ilm mRNA levels, and the clones with normal mRNA level may nevertheless contain decreased topo II enzyme activity (Eijdems et al, 1995b …”
Section: Discussionmentioning
confidence: 99%
“…Aberantna metilacija APC promotora 1A, RAR beta promotora P2, RASSF1A promotora povezana je sa gubitkom njegove genske ekspresije kod SCLC, ukazuju}i na fundamentalnu ulogu epigenetskih promena u patogenezi ove maligne bolesti. Implikacija ovih epigenetskih promena za dijagnozu i le~enje SCLC nije jo{ uvek odre|ena (72)(73)(74)(75)(76)(77).…”
Section: Markeri Metilacije Kod Tumora Plu}aunclassified